Correction to: Health effects of nutrients and environmental pollutants in Baltic herring and salmon: a quantitative benefit-risk assessment - Jouni T. Tuomisto; Arja Asikainen; Päivi Meriläinen; Päivi Haapasaari (BMC, 2020)
It was highlighted that the original article [1] contained a formatting error in the equations.